The influence of state dependent short range correlations on the depletion of the nuclear Fermi sea - Lalazissis, G. A.; Massen, S. E.; Panos, C. P. (HNPS Advances in Nuclear Physics, 2020)
The influence of state dependent short range correlations on the occupation numbers of the single particle shell model orbits of the doubly closed shell nuclei 16O and 40Ca is examined. The study shows that the effect of the state dependence of the short range correlations is rather small. The total depletion of the nuclear Fermi sea changes slightly compared with the one calculated by considering state independent short range correlations.